After the grizzly : endangered species and the politics of place in California - Alagona, Peter S. (University of California Press, 2013)
This book traces the history of threats to species and habitat in California, from the time of the gold rush to the present. The author shows how, over the course of more than a century, scientists and conservationists came to view the fates of endangered species as dependent on the ecological conditions and human activities in the places where those species lived. The story begins with the tale of the the state's extinct mascot, the California grizzly, and the conservation movements and laws that followed its disappearance. The second half of the book focuses on four high-profile endangered species: the California condor, the desert tortoise, the San Joaquin kit fox, and the Delta smelt. The author offers an account of how Americans developed a civil system in which imperiled species serve as proxies for broader conflicts about the politics of place. The book concludes that the challenge for conservationists in the twenty-first century will be to expand habitat conservation beyond protected wildlands to build more diverse and sustainable landscapes.